EFEKTIVITAS PELAYANAN PENCATATAN NIKAH DI KUA KECAMATAN BALIKPAPAN SELATAN SETELAH DIBERLAKUKANNYA INSTRUKSI DIRJEN BIMAS ISLAM NOMOR DJ.II/1 TAHUN 2015 - Shaleh Shaleh (Al-Usroh : Jurnal Hukum Keluarga Islam, 2023)
The background of this research is the implementation of the Director General of Islamic Guidance No. DJ.II/1 the Year 2015 Instruction which deactivates the Assistant of Marriage Registrar or "Penghulu" in marriage and divorce services in all sub-district Religious Affairs Offices except for those classified as D-1 and D-2. South Balikpapan District Religious Affairs Office is classified as B with a monthly average of 70-90 marriage events, while the number of "Penghulu" in charge of attending and witnessing marriage contracts is only one person. This research aims to determine the obstacles in implementing the Director General of Islamic Guidance No. DJ.II/1 theYear 2015 Instruction in South Balikpapan District Religious Affairs Office and the effectiveness of marriage registration services in South Balikpapan District Religious Affairs Office after the implementation of the instruction. The type of this research is analytical descriptive with a qualitative descriptive research method, which produces descriptive data in the form of written and spoken words as well as observed behaviors. The data collection techniques used were observation, interviews, and documentation. The qualitative data analysis technique was conducted by working with the data, organizing it, breaking it down into manageable units, synthesizing it, identifying patterns, identifying important aspects to be studied, and deciding what can be reported to others. The researcher applied the methods presented by Miles and Huberman, particularly the data reduction phase, collecting and selecting data, and focusing on important parts. After the data visualization phase, the researcher analyzed the selected and collected data and concluded. In the process of concluding, the researcher used an inductive method, which is to draw conclusions based on specific data analyzed and general conclusions from observations, interviews, and documents. The findings of this research indicate that the obstacles in implementing the Director General of Islamic Guidance (Dirjen Bimas Islam) Instruction No. DJ.II/1 of 2015 at the Office of Religious Affairs in South Balikpapan Sub-District is the lack of human resources among the marriage officials and administrators, resulting in a heavy workload and the erosion of local wisdom. However, the marriage registration service at the Office of Religious Affairs in South Balikpapan Sub-District runs quite effectively according to the ten service quality indicators proposed by Zeithaml.